Removal of aluminium from drinking water - Mohamad Nasir Othman,; Md. Pauzi Abdullah,; Yang Farina Abd. Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Aluminium in drinking water comes from natural sources and the alum used as coagulant in the water treatment process. Exposure to aluminium has been implicated in dialysis dementia, Parkinson and Alzheimer’s disease. Drinking water containing aluminium was considered to be one of the main sources of Al intake into human body. For this reason, the removal of aluminium from drinking water is vital to our health. In this study, removal of aluminium was carried out by using a chelating resin. To achieve the purpose, two chelating resin iontosorb oxin (IO) and polyhydroxamic acid (PHA) were used. The effects of concentration, pH, stirring time and resin amount was investigated. The concentration range varied between 10 and 500 ppb, pH range was between 2 and 12, stirring time between 5 and 60 minutes, and resin amount between 100 and 1500 mg. The optimum conditions of these resins were determined in a batch system. The results obtained showed that the optimum condition to remove aluminium for polyhydroxamic acid and iontosorb was pH 5-8 and pH 4-9; concentration range between 50-500 ppb, and 150-500 ppb, resin amount 200 mg and the stirring time was 20 minutes, respectively.